2022
DOI: 10.1038/s42003-022-03966-w
|View full text |Cite
|
Sign up to set email alerts
|

A magnetic antibody-conjugated nano-system for selective delivery of Ca(OH)2 and taxotere in ovarian cancer cells

Abstract: An efficient strategy for cancer therapy is presented, in which a tumor mass is initially pretreated with calcium hydroxide, then treated with Taxotere (TXT). In this regard, an advanced delivery system based on iron oxide nanoparticles has been designed. The surface of nanoparticles was functionalized with sortilin (SORT-1, a human IgG1 monoclonal antibody) that specifically encodes caov-4 ovarian cancerous cells. Plasmonic heating of the incorporated gold nanoparticles in polyvinyl alcohol (PVA) has been exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…The SEM images revealed that uniformity in the size of the VAN@Fe 3 O 4 /MOF-199 particles has been affected through coating of the surfaces by the BCD-Gn hanks. In the soild state, this is ascribed to unavoidable particle aggregation due to jelly nature of the BCD matrix and super-paramagnetic behavior of the iron oxide nanoparticles . According to the previous observations in similar cases, this aggregation is reduced to a very good extent through dispersion of the particles with the ultrasonication in a suspension state .…”
Section: Resultsmentioning
confidence: 99%
“…The SEM images revealed that uniformity in the size of the VAN@Fe 3 O 4 /MOF-199 particles has been affected through coating of the surfaces by the BCD-Gn hanks. In the soild state, this is ascribed to unavoidable particle aggregation due to jelly nature of the BCD matrix and super-paramagnetic behavior of the iron oxide nanoparticles . According to the previous observations in similar cases, this aggregation is reduced to a very good extent through dispersion of the particles with the ultrasonication in a suspension state .…”
Section: Resultsmentioning
confidence: 99%
“…While addition of a drop of ammonia solution, black particles were immediately appeared conrming successful formation of Fe 3 O 4 nanoparticles. [60][61][62] Aer completion of the addition, the mixture was well homogenized via stirring for 45 min, at room temperature. The formed Fe 3 O 4 /HNTs particles were separated by holding a super-magnet at the end of container.…”
Section: Preparation Methodsmentioning
confidence: 99%
“…The Fe 3 O 4 NPs (obtained through the co-deposition technique) were coated with a silica network and encapsulated through PVA taking advantage of H-binding interactions between hydroxyl groups, PVA structure, and Fe 3 O 4 /SiO 2 surfaces. The therapeutic was reported to be effective in selective drug delivery in ovarian cancer cells [ 66 ]. In addition to their use in cancer treatment, polymer–magnetic hybrid nanostructures have also been explored for use in drug delivery and imaging applications.…”
Section: Magnetic Nanomaterials and Their Magnetic Hybrids Nanostruct...mentioning
confidence: 99%